2013
DOI: 10.1111/apa.12325
|View full text |Cite
|
Sign up to set email alerts
|

COMFORT behaviour scale and skin conductance activity: what are they really measuring?

Abstract: All scale indicators were related to skin conductance activity in all periods, indicating pain perception. Facial tension was the most efficient indicator, while others varied in performance after painful events and possibly indicated stress after trauma. These results are discussed from a phenomenological approach and in an anxiety paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…SCA has been used in several studies to measure pain. One study reported that SCA was related to the COMFORT behaviour scale measurements, mostly facial tension, indicating pain perception . Eriksson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCA has been used in several studies to measure pain. One study reported that SCA was related to the COMFORT behaviour scale measurements, mostly facial tension, indicating pain perception . Eriksson et al.…”
Section: Discussionmentioning
confidence: 99%
“…SCA has been used in several studies to measure pain. One study reported that SCA was related to the COMFORT behaviour scale measurements, mostly facial tension, indicating pain perception (28). Eriksson et al (18) reported that both the Premature Infant Pain Profile scores and the skin conductance and peaks per second index were significantly higher during blood sampling than before or after.…”
Section: Discussionmentioning
confidence: 99%
“…Data Measurement methods extend from physiological reactions (heart and/or respiratory rates, O2 saturation: Gaspardo et al, 2008;Gibbins et al, 2008;Johnston, Stevens, Yang, & Horton, 1995;Owens & Todt, 1984), hormonal changes (beta endorphin and cortisol concentrations: Giannakoulopoulos et al, 1994;Gitau et al, 2002), electrophysiological responses (skin conductance: Harrison et al, 2006;Tristão et al, 2013), cortical activity (electroencephalogram: Draganova et al, 2005;Fabrizi et al, 2011;Starr et al, 1977), to behavioral responses (Bertoncini et al, 1989;Schaal et al, 1998). As already stated, expected responses should be adapted to the subject's characteristics.…”
Section: Experimental Measures and Proceduresmentioning
confidence: 99%
“…At birth, newborns must be able to breathe through their nose, to feed by suckling, and to tolerate light. Background noise heterogeneity and temperature variations are also novel experiences in addition to many routine procedures performed after birth, such as administrating eye drops, taking blood samples, and other manipulations (diaper change, baths) that are sources of novel sensory stimulations which must be taken carefully into consideration in relation to their impact on newborns' welfare (Gibbins et al, 2008;Mörelius, Hellström-Westas, Carlén, Norman, & Nelson, 2006;Owens & Todt, 1984;Tristão, Garcia, de Jesus, & Tomaz, 2013). In the past, invasive manipulations were performed without apprehension as newborns were considered to be insensitive to pain (Anand & Hickey, 1987).…”
mentioning
confidence: 99%
“…Some others authors also assessed the comfort of neonates by using the CS (Blauer, ; Cury, Martinez, & Carlotti, ; Franck, Ridout, Howard, Peters, & Honour, ; Van Dijk et al., ; Wielenga, de Vos, de Leeuw, & de Haan, ), Comfort Neo Scale (Monique Van Dijk et al., ), Modified Comfort Scale (Gjerstad, Wagner, Henrichsen, & Storm, ; Lee & Young, ) and Adapted Comfort Scale (Caljouw et al., ). We also identified the Comfort Behavioural Scale (CBS) as an adaptation of the CS, with six items and one dimension (Amigoni et al., ; Andersen, Bernklev, Langius‐Eklof, Nakstad, & Jylli, ; Bai, Hsu, Tang, & van Dijk, ; Boerlage, Ista, de Jong, Tibboel, & van Dijk, ; Boerlage et al., ; Da Costa Silva, Osório Alves, dos Santos El Halal, dos Santos Pinheiro, & Carvalho, ; De Jong, Baartmans, Tuinebreijer, & van Loey, ; De Jong et al., ; Johansson & Kokinsky, ; Tristão, Garcia, de Jesus, & Tomaz, ; Valkenburg et al., ). Lastly, the Paediatric Perioperative Comfort Instrument (PPCI), seven items (Moriber, ; a), which assess the comfort of paediatric patients after surgical procedures, was developed.…”
Section: Resultsmentioning
confidence: 99%